Perceived Discrimination Among African American Adolescents and Allostatic Load: A Longitudinal Analysis With Buffering Effects. Issue 3 (5th February 2014) - Brody, Gene H.; Lei, Man‐Kit; Chae, David H.; Yu, Tianyi; Kogan, Steven M.; Beach, Steven R. H.
Abstract : This study was designed to examine the prospective relations of perceived racial discrimination with allostatic load (AL), along with a possible buffer of the association. A sample of 331 African Americans in the rural South provided assessments of perceived discrimination from ages 16 to 18 years. When youth were 18 years, caregivers reported parental emotional support and youth assessed peer emotional support. AL and potential confounder variables were assessed when youth were 20. Latent growth mixture modeling identified two perceived discrimination classes: high and stable, and low and increasing. Adolescents in the high and stable class evinced heightened AL even with confounder variables controlled. The racial discrimination to AL link was not significant for young adults who received high emotional support.